2014
DOI: 10.1002/asi.23244
|View full text |Cite
|
Sign up to set email alerts
|

Visual information seeking

Abstract: The present study reports on the information seeking processes in a visual context, referred to throughout as visual information seeking. This study synthesizes research throughout different, yet complementary, areas, each capable of contributing findings and understanding to visual information seeking. Methods previously applied for examining the visual information seeking process are reviewed, including interactive experiments, surveys, and various qualitative approaches. The methods and resulting findings a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 45 publications
0
23
0
1
Order By: Relevance
“…Nevertheless, there is not a strong consensus on what constitutes a context, and what relationships exist between individuals' information seeking and its context (Chang and Lee, 2001). The importance of context in information-seeking behaviour and the information retrieval (IR) (Kelly, 2006) as well as the importance of understanding information seeking and retrieval within different contexts has been emphasised in a large number of previous studies as Albertson (2015) reported. However, to the best of our knowledge, there is a lack of knowledge regarding how users interact with visual search interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there is not a strong consensus on what constitutes a context, and what relationships exist between individuals' information seeking and its context (Chang and Lee, 2001). The importance of context in information-seeking behaviour and the information retrieval (IR) (Kelly, 2006) as well as the importance of understanding information seeking and retrieval within different contexts has been emphasised in a large number of previous studies as Albertson (2015) reported. However, to the best of our knowledge, there is a lack of knowledge regarding how users interact with visual search interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Albertson (2015) argues that future studies should investigate how visual information can be used to enhance users' literacy. Due to its multidimensional nature, visual information may have the potential to advance other information and collaborative processes (Albertson, 2015).…”
Section: Information and Visual Literacies Instructionmentioning
confidence: 99%
“…Similarly, Albertson (2015) argues that future studies should investigate how visual information can be used to enhance users' literacy. Due to its multidimensional nature, visual information may have the potential to advance other information and collaborative processes (Albertson, 2015). Looking at how image information is utilized in these different information contexts from a holistic view, in addition to looking at specific image retrieval scenarios and tasks, will expand the current image information research to a universal level.…”
Section: Information and Visual Literacies Instructionmentioning
confidence: 99%
“…brugerens arbejde, behov og forskningsområde. (Enser et al, 2007;Andre et al, 2009;Chung and Yoon, 2011;Yoon, 2011b;Reilly and Thompson, 2014;Albertson, 2015) Konkluderende ses der ikke store forandringer i forskningsfokus i artiklerne. Litteraturoversigten viser dog, at billedindeksering nu også inkluderer modeller, motivation for tagging, crowdsourcing, redigering af klassifikationssystemer og tesaurusser, som også har betydet en øget brugerinvolvering i indekseringsprocessen.…”
Section: Metoder Og Analyseunclassified